Green Human Resources Management Integration with Employee Performance and Training Development Function of the Energy Sector: Strategy Recommendations - Vardarlıer, P.; Türk, A. (Springer Science and Business Media Deutschland GmbH, 2022)
In this study, the subject of green human resource management is evaluated. By making a comprehensive analysis, it is aimed to generate strategies for the companies to increase the performance of the human resources. In this respect, the first practical strategy proposal of the study is that human resources management should both teach and learn individual behavior changes that will encourage an environmental corporate culture. In this framework, necessary investments should be made in training and development activities that will bring a collective awareness, and by supporting employee participation. It is understood that the philosophy of green human resources management is one of the essential management practices for an energy sector and this philosophy should be evaluated within the shared values through human resources management. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Green Hr; Human Quality; Human Resources; Personnel Motivation